2015
DOI: 10.1002/pola.27890
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene‐b‐poly(2,2,2‐trifluoroethyl acrylate)‐b‐polystyrene copolymers: Synthesis and fabrication of their hydrophobic porous films, spheres, and fibers

Abstract: New block copolymers Polystyrene-b-poly (2,2,2trifluoroethyl acrylate)-b-Polystyrene (PS-PTFEA-PS) with controlled molecular weight (M n 55000-11000 gÁmol 21 ) and narrow molecular weight distribution (M w /M n 51.13-1.17) were synthesized via RAFT polymerization. The molecular structure and component of PS-PTFEA-PS block copolymers were characterized through 1 H NMR, 19 F NMR, GPC, FT-IR and elemental analysis. The porous films of such copolymers with average pore size of 0.80-1.34 lm and good regularity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Up to now, a lot of polymers with different topological structures have been investigated in the BF process, including star‐shaped polymers, 18,32,33 dendrimers, 34 comb‐like polymers, 35 rod–coil block copolymers, 36,37 and linear polymers 38–43 . Apart from topology, the chemical composition of polymers also shows great impact on their self‐assembly behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, a lot of polymers with different topological structures have been investigated in the BF process, including star‐shaped polymers, 18,32,33 dendrimers, 34 comb‐like polymers, 35 rod–coil block copolymers, 36,37 and linear polymers 38–43 . Apart from topology, the chemical composition of polymers also shows great impact on their self‐assembly behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31] Up to now, a lot of polymers with different topological structures have been investigated in the BF process, including star-shaped polymers, 18,32,33 dendrimers, 34 comb-like polymers, 35 rod-coil block copolymers, 36,37 and linear polymers. [38][39][40][41][42][43] Apart from topology, the chemical composition of polymers also shows great impact on their self-assembly behavior. Ji et al reported that the Di Zhou and Bai-Heng Wu contributed equally to this work.…”
mentioning
confidence: 99%
“…The morphology of BFAs relies on the nucleation and growth of water droplets, which are susceptible to experimental parameters, such as relative humidity, concentration, polymer type, and polymer composition. With an optimized static BF process, the uncertainties have been further minimized to tolerate various casting conditions and facilitate the formation of ordered BFAs on a large scale. …”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] For example, polystyrene-b-poly(trifluoroethyl acrylate)-b-polystyrene copolymers were synthesized via RAFT polymerization to prepare ordered hydrophobic porous films via static breathing patterns. 17 Poly(acrylic acid)-b-poly(heptafluorobutyl acrylate)-b-poly(acrylic acid) triblock copolymers, made by RAFT emulsion polymerization, were used to obtain transparent films with excellent mechanical and optical properties. 18 Poly(tert-butylacrylate)-b-poly(trifluoroethyl acrylate)-b-poly(tert-butylacrylate) copolymers were synthesized by RAFT and used to prepare micelles of different sizes and morphologies in THF/water mixtures.…”
Section: Introductionmentioning
confidence: 99%